Mapping, Data, and Visualization in Digital Humanities: A Review - Akshi Katoch Pathania, (AG Volumes, 2025)
This review explores the role of mapping, data, and visualization within the field of Digital Humanities (DH), emphasizing how computational tools have transformed humanities research. It examines the use of digital mapping to study spatial relationships, visualization techniques to interpret large datasets, and diverse forms of digital data derived from cultural artifacts. The review highlights key tools and software that support timelines, mapping, and data visualization, while also addressing critical perspectives on bias and interpretation. Overall, the study underscores the interdisciplinary nature of DH and its growing impact on research, teaching, and knowledge dissemination.